Groupsourcing: Distributed Problem Solving Using Social Networks - Chamberlain, Jon (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2014)
Crowdsourcing and citizen science have established themselves in the mainstream of research methodology in recent years, employing a variety of methods to solve problems using human computation. An approach described here, termed "groupsourcing", uses social networks to present problems and collect solutions. This paper details a method for archiving social network messages and investigates messages containing an image classification task in the domain of marine biology. In comparison to other methods, groupsourcing offers a high accuracy, data-driven and low cost approach.